Multi-mode geometrically gated encryption with 4D morphing hydrogel - Xin Wen; Kaihang Zhang; Baoyi Wu; Guancong Chen; Ning Zheng; Jingjun Wu; Xuxu Yang; Tao Xie; Qian Zhao (Nature Communications)
Abstract Leveraging the rich stimuli-response of polymers represents a promising direction towards optical communication/encryption. Sign language, which relies on specific geometric change for secured communication, has been widely used for the same purpose since ancient time. We report a strategy that combines both in a validated manner with a hydrogel that not only carries encrypted optical information but also has the hidden behavior to morph geometrically. In particular, the shape morphing behavior is programmable by controlling the oriented state of the polymer chain in the thermo-responsive network. Whether the shape morphing direction is positive (bending) or negative (flattening) cannot be predicted when the polymerization methods are not informed, revealing a hidden manner. Through deciphering the coupling of chain elastic stresses and thermo-induced deswelling stress, the hydrogel can perform designed and diversified 4D morphing which represents evolution of 3D geometries with time as the fourth dimension. Consequently, the corresponding optical information can be gated based on these geometric features, thereby decrypting the correct permutation of information. Our approach that utilizes the geometric 4D morphing for gated verification of optical information offers a strategy for enhancing the security of communication in ways that are quite different from existing strategies.